The technology landscape for detection of DNA methylation in cancer liquid biopsies - Isabelle Neefs; Joe Ibrahim; Marc Peeters; Guy Van Camp; Ken Op de Beeck (Epigenetics)
DNA methylation is a well-studied epigenetic factor and has become a powerful player in the cancer biomarker research field. Together with the rising interest in methylation biomarkers, the technological advances for the detection of DNA methylation have been immense. This has led to a plethora of different methods. The first methods were established for DNA methylation detection in genomic DNA, while new methods have focused more on compatibility with the emerging interest of cell-free DNA (cfDNA) from liquid biopsies. As DNA methylation detection in cfDNA brings its own challenges, a shift from the gold standard bisulfite conversion towards enzymatic conversion methods can be observed in recent years. In this review, we aim to summarize the classic and more recent DNA methylation detection methods for liquid biopsies. Importantly, the few existing European Certified In Vitro Diagnostics (CE-IVD) clinical applications for liquid biopsies are also described, underlining the potential of DNA methylation as a detection biomarker in cfDNA. Furthermore, we provide some insights into how the field might evolve in the future, where we believe enzymatic conversion might become a new gold standard and direct sequencing methods, such as ONT-sequencing, will get an important place in the epigenetic research field. Lastly, we believe that multi-omics technologies, which can combine diverse types of biomarkers, will most likely become more important in future clinical applications. Moreover, novel recent technologies are being developed and show promising clinical applications. Taken together, methylation biomarkers are becoming more important for clinical implementation.